2020
DOI: 10.1177/1609406920938958
|View full text |Cite
|
Sign up to set email alerts
|

Documenting Syrian Refugee Children’s Memories: Methodological Insights and Further Questions

Abstract: Several scholars advocate for children’s experiences to be articulated by children themselves, and some have offered strategies on how to facilitate this. Yet there are hardly any studies that record children’s memories while they are children and offer methodological guidance on how to do so. None that we know of have recorded the unique memories of Syrian refugee children, possibly because of ethical, relational, and practical challenges of working with children considered especially vulnerable due to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…The purpose of each of these papers is to support the findings of the observations and interviews. Research that generates a variety of data types can boost the quantity and quality of research data (Ali & Gibran, 2020).…”
Section: Data Collectionmentioning
confidence: 99%
“…The purpose of each of these papers is to support the findings of the observations and interviews. Research that generates a variety of data types can boost the quantity and quality of research data (Ali & Gibran, 2020).…”
Section: Data Collectionmentioning
confidence: 99%
“…Their reactions seemed to show they expected to continue our relationship after the research concluded. My interests and those of the refugee children did not align, similar to Ali and Gibran’s (2020) observations. They found that researchers need to “make difficult choices to live with the ethical discomfiture that remains” (p. 7), balancing cultural and professional norms.…”
Section: Introductionmentioning
confidence: 54%
“…Research conducted with refugee families needs to account for unique family situations and structural contexts that may imply vulnerabilities (Ali & Gibran, 2020). We therefore decided to obtain informed consent orally in the families' first languages before the interviews and observations, emphasizing the voluntary nature of participation and the option of terminating it at any point in time without losing the offered compensation of €60.…”
Section: Study Design and Research Questionsmentioning
confidence: 99%
“…La investigación con familias refugiadas debe tener en cuenta situaciones familiares únicas y contextos estructurales que pueden implicar diversas vulnerabilidades (Ali & Gibran, 2020). Por lo tanto, decidimos obtener el consentimiento informado oral en la lengua materna de las familias participantes antes de realizar las entrevistas y observaciones, haciendo hincapié en el carácter voluntario de la participación y dando la opción de poner fin a la misma en cualquier momento sin riesgo de perder la compensación que ofrecíamos de €60.…”
Section: Puesta En Práctica De Un Estudio De Evaluación Basado En Mét...unclassified